2020
DOI: 10.1002/chem.202000572
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear ZnII Complexes Exhibiting Thermally Activated Delayed Fluorescence and Luminescence Polymorphism

Abstract: Zn II complexes exhibiting strong emission in the solid state remain scarce, and most of them exhibit only promptf luorescence. Herein the synthesis, structures, and photoluminescence properties of two Zn II complexesc ontaining new donor-acceptor ligands is reported. The new Zn II complexes have dinuclears tructures in which each metal ion adopts ad istorted square-pyramidal geometry. The Zn II complexes show strong emission in the solid state with quantum yields up to 50 %. Variable-temperature transient pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
(19 reference statements)
0
20
0
Order By: Relevance
“…In 2020, Yang et al reported two dinuclear Zn complexes (Figure 8a, Zn3 and Zn4) with TADF and luminescence polymorphism. [41] But there is limited change when compared ligands between the dinuclear Zn complexes in this work and mononuclear Zn complexes reported by Adachi, [40] suggesting that the imine ligands apparently play a vital role in the formation of different coordination modes. As shown in Figure 8b, in the powder state, Zn3 and Zn4 exhibited strong yellow and green emission with PLQYs of 13% and 50% respectively, accompanied by short delayed fluorescence lifetime below 2.5 μs.…”
Section: Other Non-precious Metal Complexesmentioning
confidence: 58%
“…In 2020, Yang et al reported two dinuclear Zn complexes (Figure 8a, Zn3 and Zn4) with TADF and luminescence polymorphism. [41] But there is limited change when compared ligands between the dinuclear Zn complexes in this work and mononuclear Zn complexes reported by Adachi, [40] suggesting that the imine ligands apparently play a vital role in the formation of different coordination modes. As shown in Figure 8b, in the powder state, Zn3 and Zn4 exhibited strong yellow and green emission with PLQYs of 13% and 50% respectively, accompanied by short delayed fluorescence lifetime below 2.5 μs.…”
Section: Other Non-precious Metal Complexesmentioning
confidence: 58%
“…Recently, thermally activated delayed fluorescent (TADF) emitters consisting of pure organic compounds based on carbon (C), nitrogen (N), oxygen (O), and sulfur (S) have been considered as an attractive technology to convert all the molecular excitons to light with a 100 % internal quantum efficiency without the use of noble metals [9–21] . Although a large number of purely organic TADF emitters have been reported, metal complex‐based TADF emitters without using transition metal elements, such as noble metals, have been rarely explored [23, 32] . Different from conventional TADF emitters, the expected features of the metal complex‐based TADF emitters are as follows: (i) enhancement in thermal stability and molecular rigidity by ligandation and rigidification; (ii) improvement in photoluminescence quantum yield (PLQY) by strengthening the acceptor ability and the molecular rigidity; (iii) expected reduction in singlet ( E S ) and triplet ( E T ) energy gaps (Δ E ST ) by changing the acceptor character of conjugated ligand; (iv) shortening of the decay lifetime by heavy atom effect.…”
Section: Introductionmentioning
confidence: 99%
“…Adachi and co‐workers attempted to prepare mononuclear Al complexes, but they could only obtain dinuclear Al complexes bridged by OH groups. Very recently, Yang and co‐workers reported dinuclear Zn complexes exhibiting TADF and luminescence polymorphism [32] . These Zn complexes exhibit strong emission in the powder state with a PLQY of 50 % and a short τ DF below 2.5 μs.…”
Section: Introductionmentioning
confidence: 99%
“…Different from conventional TADF emitters, the expected features of the metal complex‐based TADF emitters are as follows: (i) enhancement in thermal stability and molecular rigidity by ligandation and rigidification; (ii) improvement in photoluminescence quantum yield (PLQY) by strengthening the acceptor ability and the molecular rigidity; (iii) expected reduction in singlet ( E S ) and triplet ( E T ) energy gaps (Δ E ST ) by changing the acceptor character of conjugated ligand; (iv) shortening of the decay lifetime by heavy atom effect. However, except for noble metal complexes, [22–33] only a handful of mononuclear metal complexes have been reported so far, including zinc (Zn), lithium (Li), and magnesium (Mg). For example, Adachi and co‐workers reported the first example of a Zn complex with a TADF molecule as a ligand exhibiting a high PLQY of 78 % with a long delayed fluorescence lifetime ( τ DF ) of 37.8 μs, and a maximum external quantum efficiency (EQE) of 19.6 % in OLEDs [23] .…”
Section: Introductionmentioning
confidence: 99%